Pengembangan Nilai Karakter Siswa dalam Pendidikan Agama Islam dan Budi Pekerti Pada Kurikulum 2013 - Werdiningsih, Wilis (IAIN Ponorogo, 2017)
Character education becomes urgent considering that Indonesia has been experiencing moral degradation. The 2013 curriculum requires all subject teachers to pay more attention to the affective aspect. In Kurtilas, there is an increase in the number of hours on the subjects of PAI (Islamic education) and Budi Pekerti (Moral) in public schools. This study aims to examine the development of character values of junior high school students in the subjects of PAI and Budi Pekerti in the 2013 curriculum. A library research method was employed covering four steps, namely data collection, data reduction, inference and data analysis to extract information from various literatures related to character education, curriculum structure of PAI and Budi Pekerti at SMP level as well as the contents of character education. The results showed that there were character values on each basic competence (KD) on the subjects of PAI and Budi Pekerti. Character values included religious, discipline, tolerance, responsibility, respect, self-control and peace. The implementation could be done by designing better instructions of PAI and Budi Pekertiby choosing the right approach and method.Ø£ØµØ¨ØØª Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ®ÙÙÙØ© ÙØ§Ù ÙØ© ÙÙ Ø§ Ø£ØµØ§Ø¨ Ø¥ÙØ¯ÙÙÙØ³ÙØ§ Ù Ù Ø§ÙØØ·Ø§Ø· Ø®ÙÙÙÙ.Â Ø§ÙØªØ¶Ù Ø§ÙÙ ÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³Ù 2013 Ø¬Ù ÙØ¹ Ù Ø¯Ø±ÙØ³Ù Ø§ÙÙ ÙØ§Ø¯ Ø§ÙØ¯Ø±Ø§Ø³ÙØ© Ø£Ù ÙÙØªÙ ÙØ§ Ø£ÙØ«Ø± Ø¨Ø§ÙØ¬Ø§ÙØ¨ Ø§ÙØ¹Ø§Ø·ÙÙ. ÙØ§ÙØª ÙÙ Ø§ÙÙ ÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³Ù 2013 Ø²ÙØ§Ø¯Ø© Ø³Ø§Ø¹Ø§Øª Ø£Ù ØØµØµ ÙØªØ¹ÙÙÙ Ù Ø§Ø¯Ø© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© ÙØ§ÙØ£Ø®ÙØ§Ù ÙÙ Ø§ÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ¹Ø§Ù Ø©. ÙÙØ¯Ù ÙØ°Ø§ Ø§ÙØ¨ØØ« Ø¥ÙÙ Ø¯Ø±Ø§Ø³Ø© ØªÙÙ ÙØ© Ø§ÙÙÙÙ Ø§ÙØ£Ø®ÙØ§ÙÙØ© ÙØ·ÙØ§Ø¨ Ø§ÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙÙ ØªÙØ³Ø·Ø© Ø§ÙØ¹Ø§Ù Ø© ÙÙ Ù Ø§Ø¯Ø© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© ÙØ§ÙØ£Ø®ÙØ§Ù ÙÙ Ø§ÙÙ ÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³Ù 2013.Â Ø§Ø³ØªØ®Ø¯Ù Ø§ÙØ¨Ø§ØØ« Ù ÙÙØ¬ Ø§ÙØ¨ØØ« Ø§ÙÙ ÙØªØ¨Ù ÙÙÙ ÙØØªÙÙ Ø¹ÙÙ Ø£Ø±Ø¨Ø¹ Ø®Ø·ÙØ§Øª : Ø¬Ù Ø¹ Ø§ÙØ¨ÙØ§ÙØ§ØªØ ÙØªØ®ÙÙØ¶ Ø§ÙØ¨ÙØ§ÙØ§ØªØ ÙØ§ÙØ§Ø³ØªØ¯ÙØ§Ù ÙØªØÙÙÙ Ø§ÙØ¨ÙØ§ÙØ§Øª ÙÙØØµÙÙ Ø¹ÙÙ Ø§ÙÙ Ø¹ÙÙÙ Ø§Øª Ù Ù Ø§ÙÙ ØµØ§Ø¯Ø± Ø§ÙÙ ØªÙÙØ¹Ø© Ø§ÙÙ ØªØ¹ÙÙØ© Ø¨Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ®ÙÙÙØ©Ø ÙÙÙÙÙ Ø§ÙÙ ÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³Ù ÙÙ Ø§Ø¯Ø© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© Ù Ø§ÙØ£Ø®ÙØ§Ù ÙÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ¹Ø§Ù Ø© ÙÙ Ø¶Ù ÙÙ ÙÙÙ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ®ÙÙÙØ© ÙÙÙ. Ø¯ÙØª ÙØªØ§Ø¦Ø¬ Ø§ÙØ¨ØØ« Ø¹ÙÙ Ø£Ù ÙÙÙ ÙÙÙ Ø£Ø®ÙØ§ÙÙØ© ÙÙ ÙÙ Ù Ù Ù Ø¹Ø§ÙÙØ± Ø§ÙÙÙØ§Ø¡Ø© ÙÙ Ù Ø§Ø¯Ø© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© ÙØ§ÙØ£Ø®ÙØ§Ù. ÙÙØ°Ù Ø§ÙÙÙÙ Ø§ÙØ®ÙÙÙØ© Ù ÙÙØ§ : Ø§ÙØ¯ÙÙÙØ©Ø ÙØ§ÙØ§ÙØ¶Ø¨Ø§Ø·Ø ÙØ§ÙØªØ³Ø§Ù ØØ ÙØ§ÙÙ Ø³Ø¤ÙÙÙØ©Ø ÙØ¥ÙØ±Ø§Ù Ø§ÙØºÙØ±Ø ÙØ¶Ø¨Ø· Ø§ÙÙÙØ³ ÙØØ¨ Ø§ÙØ³ÙØ§Ù . ÙØ§ÙØªØ·Ø¨ÙÙ Ù Ù ÙØ°Ø§ ÙÙ ÙÙ Ø§ÙÙÙØ§Ù Ø¨Ù Ø¹Ù Ø·Ø±ÙÙ Ø§ÙØªØµÙ ÙÙ Ø§ÙØ£Ø¬ÙØ¯ ÙØªØ¹ÙÙÙ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© ÙØ§ÙØ£Ø®ÙØ§ÙØ ÙÙØ°Ø§ Ø¨Ø§Ø®ØªÙØ§Ø± Ø§ÙÙ Ø¯Ø®Ù ÙØ§ÙØ·Ø±ÙÙØ© Ø§ÙÙ ÙØ§Ø³Ø¨ÙÙ.